2017
DOI: 10.5005/jp-journals-10024-2135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Proinflammatory Cytokine Levels in Gingival Crevicular Fluid around Dental Implants with Ceramic and Titanium Abutments

Abstract: Background: Considering the high success rate of osseointegration, there is ever-increasing use of dental implants. The mechanisms and biologic response of peri-implant tissues are different depending on the biocompatibility of the implant material. The aim of this study was to compare the proinflammatory cytokine levels in the gingival crevicular fluid (GCF) around dental implants with ceramic and titanium abutments. Materials and methods:All the patients with dental implants referring to two private offices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
(20 reference statements)
0
12
0
2
Order By: Relevance
“…They showed that levels of IL-1β and IL-6 in the GCF around ceramic abutments were significantly lower in comparison with titanium implants. 20 Abdulwassie and Dhanrajani 21 analyzed patients undergoing dental implant procedures in a retrospective study. They prescribed amoxicillin to all the patients and carried it for 10 days postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that levels of IL-1β and IL-6 in the GCF around ceramic abutments were significantly lower in comparison with titanium implants. 20 Abdulwassie and Dhanrajani 21 analyzed patients undergoing dental implant procedures in a retrospective study. They prescribed amoxicillin to all the patients and carried it for 10 days postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that central obesity and decompensated heart failure can intensify the risk of OSA. [7,8,27,28] A definitive diagnosis of OSA is done by polysomnography, but this method is time-consuming and requires special laboratory measures, so OSA remains unknown and is not treated in most cases. This method is based on the number of abnormal breathing events that occur every hour of sleep, which is referred to as the apnea-hypopnea index (AHI).…”
Section: Research Articlementioning
confidence: 99%
“…[8,[25][26][27][28][29] The intrastriatal injection of 6-hydroxydopamine (6-OHDA) at a predetermined dosage in rats results in progressive and gradual loss of dopaminergic neurons in the substantia nigra whose trend is similar to the neuropathology of the Parkinson's disease and is considered as a valid empirical model for showing the stages of the onset of the disease. [9,[30][31][32][33][34] The neurotoxin 6-OHDA through producing free radicals, which in turn have cytotoxic effect, disrupts calcium homeostasis by increasing the penetration or exacerbation of release from intracellular reserves, [10,35,36] affecting the genetic regulation and induction of apoptosis [11,[37][38][39][40] and causing neuronal death. For the last three decades, levodopa has been employed as the best medicine for Parkinson's treatment.…”
Section: Research Articlementioning
confidence: 99%